Physics of semiconductor devices - Sze, S. M.; Li, Yiming; Ng, Kwok K. (New Jersey : Wiley, 2021)
"Since the discovery of the transistor effect in 1947 by a research team at Bell Telephone Laboratories (now Nokia Bell Labs.), the semiconductor-device field has grown rapidly. Coincident with this growth, the semiconductor-device literature has expanded and diversified. For access to this massive amount of information, there is a need for a book giving a comprehensive introductory account of device physics and operational principles, with references. With the intention of meeting such a need, the First, Second and Third Editions of Physics of Semiconductor Devices were published in 1969, 1981 and 2007, respectively. It is perhaps somewhat surprising that the book has so long held its place as one of the main textbooks for advanced undergraduate and graduate students in applied physics, electrical and electronics engineering, and materials science. Because the book includes much useful information on material parameters and device physics, it is also a major reference for engineers and scientists in semiconductor-device research and development. To date, the book is one of the most, if not the most, cited works in contemporary engineering and applied science publications with over 55,000 citations (Google Scholar)"--
Includes bibliographical references and index.
Keywords: Semiconductors